Overlapping Clinical Manifestations of Multisystem Inflammatory Syndrome in Children with Other Endemic Diseases of Pakistan: A Case Report - Anam Zafar; Sughra Wahid; Asad Ullah; Hassan Mumtaz (European Medical Journal)
Multisystem inflammatory syndrome (MIS-C) is a challenging disease associated with COVID-19. Clinical manifestation of MIS-C may mimic many endemic illnesses of tropical and subtropical countries, making early diagnosis more difficult. The authors present the case of an 8-year-old who presented with non-specific febrile illness which was managed as extensively drug-resistant typhoid with meropenem. The patient developed abdominal pain and hypotension during the hospital stay. Surgical causes were ruled out and managed with fluid protocol of dengue shock syndrome on the basis of falling platelets and fluid leak on ultrasound. But refractory condition and new-onset cardiac dysfunction prompted alternate diagnosis. Diagnostic criteria of MIS-C were fulfilled and the patient was managed with a single dose of intravenous Ig, pulse therapy of methylprednisolone, and temporary pacemaker placement. MIS-C should be kept in the differentials of diseases with multisystem involvement in the wake of the COVID-19 pandemic, as its clinical spectrum closely mimics other endemic illnesses of tropical and subtropical regions.